89.3k views
2 votes
Solve SA = πrs + π r2 for s A) -r B) SA + r C) SA π2r3 D) SA - πr2 πr

User Eric Yuan
by
5.7k points

2 Answers

7 votes

Answer:

D

Explanation:

SA = πrs + πr²

SA - πr² = πrs

s = (SA - πr²)/πr

User Dmitry MiksIr
by
5.4k points
7 votes

Answer:

(SA - π r^2)/πr = s

Explanation:

SA = πrs + π r^2

Subtract π r^2 from each side

SA - π r^2 = πrs + π r^2-π r^2

SA - π r^2 = πrs

Divide each side by πr

(SA - π r^2)/πr = πrs/πr

(SA - π r^2)/πr = s

User MarkWalczak
by
5.6k points